1989
DOI: 10.1016/s0022-5347(17)38900-0
|View full text |Cite
|
Sign up to set email alerts
|

Serendipitous Diagnosis of Appendicovesical Fistula by Bone Scan: A Case Report

Abstract: A 71-year-old patient had recurrent urinary tract infections for 7 years after sigmoid colectomy via a Hartmann procedure. Extensive radiological and endoscopic tests were inconclusive as to the cause of bacteriuria. Chronic back pain led to performance of a radionuclide bone scan with the incidental demonstration of a vesicoenteric fistula, confirmed at exploration. Appendectomy with resection of the involved bladder resulted in cessation of bacteriuria.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

1990
1990
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 6 publications
0
5
0
Order By: Relevance
“…However, early diagnosis is difficult, because the symptoms are vague and useful diagnostic tools have not yet been identified. It has been reported that it usually has taken at least 1 year from the onset symptoms to diagnosis 5. Many diagnostic tools, such as intravenous pyelography (IVP), cystoscopy, cystography, colonoscopy, and CT scans, have been used for detecting a vesico-appendiceal fistula 3.…”
Section: Discussionmentioning
confidence: 99%
“…However, early diagnosis is difficult, because the symptoms are vague and useful diagnostic tools have not yet been identified. It has been reported that it usually has taken at least 1 year from the onset symptoms to diagnosis 5. Many diagnostic tools, such as intravenous pyelography (IVP), cystoscopy, cystography, colonoscopy, and CT scans, have been used for detecting a vesico-appendiceal fistula 3.…”
Section: Discussionmentioning
confidence: 99%
“…99m-Tc-MDP can be observed in the intestines in 1% of bone scans with a prominent localization in the ascending colon; rarely, it appears all over the intestines ( 1 ). Intense bowel accumulation of bone-seeking agents can be seen in cases of occult gastric bleeding ( 2 ), intestinal infarction ( 3 ), enterovesical fistula ( 4 ), urinary diversion surgical procedure ( 5 ), protein-losing enteropathy ( 6 ), primary intestinal lymphangiectasia ( 7 ), systemic AL amyloidosis ( 8 ), and uptake in normal intestine in children. In children, the radiotracer accumulated in the cecum is presumably secondary to concentration via water absorption.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that it usually took at least 1 year from the onset of symptom to confirmatory diagnosis. Unfortunately, it may be delayed for more than 10 years 4. Many diagnostic tools, such as intravenous pyelography (IVP), cystoscopy, barium enema, cystogram, and computed tomography (CT) scans, have been used for detecting an appendicovesical fistula.…”
Section: Discussionmentioning
confidence: 99%